Long term outcome of skull-base chondrosarcoma patients treated with high-dose proton therapy with or without conventional radiation therapy. Issue 3 (December 2018) - Weber, Damien C.; Murray, Fritz; Combescure, Christophe; Calugaru, Valentin; Alapetite, Claire; Albertini, Francesca; Bolle, Stephanie; Goudjil, Farid; Pica, Alessia; Walser, Marc; Mammar, Hamid; Bachtiary, Barbara; et al.
Abstract: Background and purpose: Skull-base chondrosarcoma (ChSa) is a rare bone tumor and the outcome of patients with this malignancy has been documented only in a limited number of series with a restricted number of patients. Objective: This study was conducted to assess the outcome and prognostic factors of a large cohort of ChSa patients treated with radiotherapy in two proton therapy centers. Materials and methods: From 1996 to 2015, 251 (male, 43.4%) patients (mean age, 42.0 ± 16.2 years) were treated with protons with ( n  = 135; 53.8%) or without photons ( n  = 116; 46.2%). Median delivered dose was 70.2 GyRBE . Failure-free survival (FFS), overall survival (OS) and CTCAE grade ≥3 toxicity free survival (TFS) were calculated using the Kaplan–Meier method. Results: After a median follow-up of 88.0 months for surviving patients, local and distant failures were observed in 12 (4.8%) and 4 (1.6%) patients, respectively. Late failures >6 years were observed in 4 (33.3%) patients. The estimated 7-year FFS was 93.1%. Twenty-five (10%) patients died. The estimated 7-year OS was 93.6%. Tumor volume ( p  = 0.006) and optic pathway compression ( p  = 0.027) were significantly associated with the risk of treatment failure on univariate analysis. Treatment failure was significantly associated with a higher risk of death (hazard ratio = 126). The estimated 7-year TFS was 84.2%. Conclusions: The outcome of skull-base ChSa patients treated with high-dose protons with or without photons is excellent, particularly for patients with small tumors with no optic pathway compression. Treatment failure was however associated with a significantly increased risk of death.